1985
DOI: 10.1128/aac.27.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro activities of aztreonam, ciprofloxacin, norfloxacin, ofloxacin, HR 810 (a new cephalosporin), RU28965 (a new macrolide), and other agents against enteropathogens

Abstract: The in vitro activity of drugs currently used in the treatment of diarrhea against 595 enteropathogens from worldwide sources was compared with that of six newly developed antibiotics, ciprofloxacin; norfloxacin; ofloxacin; aztreonam; HR810, an expanded-spectrum cephalosporin; and RU28965, a new macrolide. In contrast with ampicillin and chloramphenicol, trimethoprim-sulfamethoxazole showed an excellent activity against all of the enteropathogens tested, except Campylobacter species. Ciprofloxacin had the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…This was reported previously in C. jejuni strains by Goossens et al (1985) and by our group (Tejero et al 1996) We have previously found a low percentage (2.3%) of tetracycline resistance in strains isolated from hens (Tejero et al 1996), and in the present study only two (1.8%) out of the 108 clinical strains tested were resistant to this antibiotic. So, based on the evidence mentioned above, we can conclude that in this geographical region tetracycline is not yet a problem as it is in other countries (Taylor & Courvalin 1988, Gaudreau & Gilbert 1998, Li et al 1998.…”
supporting
confidence: 40%
“…This was reported previously in C. jejuni strains by Goossens et al (1985) and by our group (Tejero et al 1996) We have previously found a low percentage (2.3%) of tetracycline resistance in strains isolated from hens (Tejero et al 1996), and in the present study only two (1.8%) out of the 108 clinical strains tested were resistant to this antibiotic. So, based on the evidence mentioned above, we can conclude that in this geographical region tetracycline is not yet a problem as it is in other countries (Taylor & Courvalin 1988, Gaudreau & Gilbert 1998, Li et al 1998.…”
supporting
confidence: 40%
“…Little is known about the ,B-lactam susceptibility pattern of C. coli. A few studies have reported data about ampicillin (4,12,14), amoxicillin (6,14), cefotaxime (4,6,15), cephalothin (4,10,15), cefoperazone (14), and cefuroxime and penicillin G (15) susceptibility. ,B-Lactamase production was reported in 29 of 31 C coli tested by Fliegelman et al (4).…”
mentioning
confidence: 99%
“…For presumptive therapy, the quinolone class of antimicrobial agents offers the advantage of marked bactericidal activity against pathogens of bacterial enteritis, including Campylobacter spp., enterotoxigenic Escherichia coli, and Vibrio spp. (7,14). Tosufloxacin (T-3262; A-60969 HCl; A-61827 tosylate) has improved activity compared with other quinolones against gram-positive cocci and anaerobic organisms (4,6), as well as Listeria monocytogenes (4).…”
mentioning
confidence: 99%